A catalog of prominence eruptions detected automatically in the SDO/AIA 304 Å images. (1st September 2020) - Yashiro, S.; Gopalswamy, N.; Akiyama, S.; Mӓkelӓ, P.A.
Abstract: We report on a statistical study of prominence eruptions (PEs) using a catalog of these events routinely imaged by the Atmospheric Imaging Assembly (AIA) on board the Solar Dynamics Observatory (SDO) in the 304 Å pass band. Using an algorithm developed as part of an LWS project, we have detected PEs in 304 Å synoptic images with 2-min cadence since May 2010. A catalog of these PEs is made available online (https://cdaw.gsfc.nasa.gov/CME_list/autope/ ). The 304 Å images are polar-transformed and divided by a background map (pixels with minimum intensity during one day) to get the ratio maps above the limb. The prominence regions are defined as pixels with a ratio ≥2. Two prominence regions with more than 50% of pixels overlapping are considered the same prominence. If the height of a prominence increases monotonically in 5 successive images, it is considered eruptive. All the PEs seen above the limb are detected by the routine, but only PEs with width ≥15° are included in the catalog to eliminate polar jets and other small-scale mass motions. The identifications are also cross-checked with the PEs identified in Nobeyama Radioheliograph images (http://solar.nro.nao.ac.jp/norh/html/prominence/ ). The catalog gives the date, time, central position angle, latitude, and width of the eruptive prominence. The catalog also provides links to JavaScript movies that combine SDO/AIA images with GOES soft X-ray data to identify the associated flares, and with SOHO/LASCO C2 images to identify the associated coronal mass ejections. We examined the statistical properties of the PEs and found that (1) the surges generally occur only in the active region belt while prominences are found in all latitudes, and (2) the high-latitude PE speed decreased with the decreasing of the average polar magnetic field strength of the previous cycle. Highlights: An algorithm to detect prominence eruptions (PEs) automatically has been developed. A catalog of the detected PEs is available online. While prominences are found in all latitudes, the surges generally occur only in the active region belt. Shortly before the time of the polarity reversal, the speed of the prominences becomes very small. High-latitude PE speed decreased with the decreasing of the average polar magnetic field strength of the previous cycle.